Increasing the composition range of a novel τ11-Al4Fe1.7Si alloy with additions of Mn. (June 2022) - Soto-Medina, Sujeily; Rijal, Biswas; Sachdev, Anil K.; Hennig, Richard G.; Manuel, Michele V.
Abstract: Automotive applications need low-cost, lightweight, high-temperature alloys to increase vehicle efficiency. The Al–Fe–Si system provides an opportunity to develop such a material, as it consists of three low-cost elements that are all abundant in nature. Specifically, the τ11 -Al4 Fe1.7 Si ternary intermetallic phase is a high-temperature, lightweight phase with high strength and good corrosion resistance. However, this phase exhibits a narrow compositional range of stability, resulting in undesirable microstructures forming during solidification and processing, limiting its use in potential applications. Density functional theory (DFT) calculations and a thermodynamically-driven experimental approach utilizing diffusion couples were employed to study the effect of Mn on the stability and composition range of τ11 -Al4 Fe1.7 Si. The DFT calculations showed a decrease in the energy of the structure when alloying with Mn. Experimental results confirmed the predictions from the DFT calculations, indicating that alloying with Mn increases the compositional range, and thus the processability of this phase. New phase diagrams and equilibria are proposed by exploring and determining phase boundaries for the τ11 -Al4 Fe1.7 Si phase with Mn. Highlights: Phase boundary of the ternary τ11 -Al4 Fe1.7 Si was successfully expanded by additions of Mn. Phase boundary of τ11 -Al4 (Fe, Mn)1.7 Si was studied coupling computational tools with experimental methods. Results showed τ11 -Al4 Fe1.7 Si and τ8 -Al9 Mn3 Si form a solid solution, single-phase region in the Al–Fe–Si–Mn quaternary system. Phase equilibria was expanded through energetic and entropic stabilization in intermetallic.